Extrachromosomal Circular DNA: Category, Biogenesis, Recognition, and Functions - Cao, Xiukai; Wang, Shan; Ge, Ling; Zhang, Weibo; Huang, Jinlin; Sun, Wei (Frontiers in Veterinary Science, 2021)
Extrachromosomal circular DNA (eccDNA), existing as double-stranded circular DNA, is derived and free from chromosomes. It is common in eukaryotes but has strong heterogeneity in count, length, and origin. It has been demonstrated that eccDNA could function in telomere and rDNA maintenance, aging, drug resistance, tumorigenesis, and phenotypic variations of plants and animals. Here, we review the current knowledge about eccDNA in category, biogenesis, recognition, and functions. We also provide perspectives on the potential implications of eccDNA in life science.